Most ankle sprain research is either false or clinically unimportant: A 30-year audit of randomized controlled trials - Chris M. Bleakley; Mark Matthews; James M. Smoliga (Elsevier, 2021)
Background: Lateral ankle sprain is the most common musculoskeletal injury. Although clinical research in this field is growing, there is a broader concern that clinical trial outcomes are often false and fail to translate into patient benefits. Methods: We audited 30 years of experimental research related to lateral ankle sprain management (n = 74 randomized controlled trials) to determine if reports of treatment effectiveness could be validated beyond statistical certainty. Results: A total of 77% of trials reported positive treatment effects, but there was a high risk of false discovery. Most trials were unregistered and relied solely on statistical significance, or lack of statistical significance, rather than on interpreting key measures of minimum clinical importance (e.g., minimal detectable change, minimal clinically important difference). Conclusion: Future clinical trials must adopt higher standards of reporting and data interpretation. This includes consideration of the ethical responsibility to preregister their research and interpretation of clinical outcomes beyond statistical significance.